Crisis, austerity, and fiscal expenditure in Greece: recent experience and future prospects in the post-COVID-19 era - Michalis Nikiforos (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2022)
This paper provides a discussion of the relationships between austerity, the macroeconomic performance of the Greek economy, debt sustainability, and the provision of healthcare and other social services since 2010. It explains that austerity was imposed in the name of debt sustainability. However, there was a vicious cycle of recession and austerity: each round of austerity measures led to a deeper recession, which increased the debt-to-GDP ratio and therefore undermined the goal of debt sustainability and led to another round of austerity. One of the effects of the austerity policies was the significant reduction of healthcare expenditure, which made Greece more vulnerable to the recent pandemic. Finally, it shows how recent pre-COVID debt sustainability analyses projected that Greek public debt would become unsustainable even under minor deviations from an optimistic baseline. The pandemic shock will thus lead to an explosion of public debt. This brings again to the fore the need for a restructuring of Greek public debt, and other policies that will address the eurozone's structural imbalances.
Keywords: 330; Greece; public debt; austerity; healthcare; debt sustainabilityE32; E62; E63; N14